œCaring Snake & Ladder Learning Media Development For 2nd Year Students™ Competence In Reading Aloud At Mekarsari 03 Elementary School - Jannah, Putri Asnes Miftahul; Neolaka, Grace Amialia Anfetonanda (ELEMENTARY SCHOOL JOURNAL PGSD FIP UNIMED, 2023)
This study aims to describe the results of the development of the "CARING" snake and ladder media for the ability to read loudly of second-grade students at Mekarsari 03 Elementary School. The method in this research is research and development (R&D) with the ADDIE model, which refers to five stages: analysis, design, development, implementation (implementations), and evaluation. The results of the study showed that the CARING snake and ladder media received a score of 72% from media experts, 78% from material experts, 95% from students, and 100% from teachers. Based on these results, the media was valid and very feasible for use to help grade 2 students' reading aloud skills at Mekarsari 03 Elementary School. Keywords: Snake & Ladder, learning media, reading aloud, elementary school